GAMBARAN KEPERCAYAAN DIRI SISWA SMP KELAS VII - Siti Nurlaela; Heris Hendriana; Tuti Alawiyah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
The purpose of this study was to determine the description of those who have low self-confidence in class VII SMP N 6 CAMPAKA. This study uses a descriptive quantitative approach because it describes a phenomenon, event, and occurrence that occurs factually, systematically, and accurately. The research sample used was 9 students of SMP N 6 Campaka. The instrument used in this study was a questionnaire containing several questions about perceptions of the research problem. In addition to the questionnaire, there are also interview guidelines as a follow-up to the questionnaire so that the research results are more accurate. The data collected is then analyzed descriptively quantitatively. Based on the results of the analysis, there are 2% of students with a high level of self-confidence, meaning that students are able to think positively, and are active in their learning, 4% are in the low category, meaning students tend to be silent, and shy. 3% are in the medium category, students who are in the medium category tend to be open, and look relaxed. The results of this study can be concluded that self-confidence plays an important role in the continuity of learning. Keywords: Confidence, Students